Improving Early Writing Skills Through Play-Based Learning with Loose Parts: A Classroom Action Research with Children with Learning Difficulties - Utami, Sri; Purwanta, Edi (Journal of Innovation and Research in Primary Education, 2025)
Early writing skills constitute a critical foundation for literacy development, yet children with learning difficulties face substantial challenges in acquiring these competencies. This study investigated the effectiveness of play-based learning with loose parts media in enhancing early writing skills among children with learning difficulties at Permata Bunda Kindergarten, East Kutai. A classroom action research design following the Kemmis and McTaggart model was employed across two cycles. The participant was a six-year-old child with identified learning difficulties in Group B. Data were collected through early writing assessments at three time points (pre-intervention, post-cycle I, post-cycle II), systematic observations, and semi-structured interviews. The intervention comprised guided play activities using various loose parts materials including buttons, stones, and wooden shapes to form letters and words. The participant's early writing performance improved substantially from 48% (very poor) at baseline to 58% (moderate) post-cycle I, and 83% (good) post-cycle II, surpassing the 70% minimum competency standard. Improvements were observed across letter formation, word construction, and autonomous task completion. Play-based learning with loose parts media effectively enhances early writing skills in children with learning difficulties, providing an accessible, developmentally appropriate intervention approach. The iterative refinement process demonstrated the importance of responsive pedagogy incorporating motivational supports and attention management strategies for optimizing learning outcomes.